Safe Opioid Prescribing for Acute Noncancer Pain in Hospitalized Adults: A Systematic Review of Existing Guidelines. Issue 4 (1st April 2018) - Herzig, Shoshana J.; Calcaterra, Susan L.; Mosher, Hilary J.; Ronan, Matthew V.; Van Groningen, Nicole; Shek, Lili; Loffredo, Anthony; Keller, Michelle; Jena, Anupam B.; Nuckols, Teryl K.
Abstract : BACKGROUND: Pain is common among hospitalized patients. Inpatient prescribing of opioids is not without risk. Acute pain management guidelines could inform safe prescribing of opioids in the hospital and limit associated unintended consequences. PURPOSE: To evaluate the quality and content of existing guidelines for acute, noncancer pain management. DATA SOURCES: The National Guideline Clearinghouse, MEDLINE via PubMed, websites of relevant specialty societies and other organizations, and selected international search engines. STUDY SELECTION: Guidelines published between January 2010 and August 2017 addressing acute, noncancer pain management among adults were considered. Guidelines that focused on chronic pain, specific diseases, and the nonhospital setting were excluded. DATA EXTRACTION: Quality was assessed using the Appraisal of Guidelines for Research and Evaluation II (AGREE II) instrument. DATA SYNTHESIS: Four guidelines met the selection criteria. Most recommendations were based on expert consensus. The guidelines recommended restricting opioids to severe pain or pain that has not responded to nonopioid therapy, using the lowest effective dose of short‐acting opioids for the shortest duration possible, and co‐prescribing opioids with nonopioid analgesics. The guidelines generally recommended checking the prescription drug monitoring program when prescribing opioids, developing goals for patient recovery, and educating patients regarding the risks and side effects of opioid therapy. Additional recommendations included using an opioid‐dose conversion guide, avoidance of co‐administration of parenteral and oral opioids, and using caution when co‐prescribing opioids with other central nervous system depressants. CONCLUSIONS: Guidelines, based largely on expert opinion, recommend judicious prescribing of opioids for severe, acute pain. Future work should assess the implications of these recommendations on hospital‐based pain management.